Thermal Plasma Processing of Ilmenite - Samal, Sneha (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book shows how to prepare titania rich slag from metallized ilmenite using thermal plasma processing. The author reveals the development of a thermal plasma process alternative to the current used ones, which are highly energy costly. The appropriate design of the plasma reactor, which is crucial for achieving reduced energy consumption, is described in this book. The content can be of interest for industrial purposes.